Centralized and decentralized solar power control and distribution: a comparative analysis of operational and economic aspects - Mustafa, Farhana-Binte; Ahmed, Imran; MobasSharin, Md. Asra-Ye (BARC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.